(untitled) (Development Service Industry Management, 2025)
The article discusses the concept of rational nutrition in the current realities of war in Ukraine as an important factor in maintaining health and improving the quality of life, especially for people working in the scientific field. The article analyses the scientific works of domestic and foreign scientists, provides a literature review on the topic of research. The emphasis is put on the promotion of healthy nutrition in the world and in Ukraine. The sustainable approach of the catering industry to the formation of new food trends among customers, including the reduction of the consumption of animal products, the introduction of the concepts of "Zero West" and "Local Food", is analysed. The issue of improving the efficiency of mental activity through a balanced diet will be explored. The role of restaurants as a platform for the introduction of innovative food concepts such as functional food, organic and plant-based dishes, as well as the influence of restaurants in shaping the food culture of modern society, consumer choices and habits, is identified. The article highlights the impact of stress on eating behaviour and demand for restaurant services both globally and in Ukraine. Recommendations for rational nutrition during increased mental stress under conditions of prolonged stress for different age groups are provided. The article highlights the impact of meat consumption on the development of the human brain. Scientific studies on the effects of a plant-based diet on human health are presented, and recommendations for a vegan diet are described. The factors that have influenced the popularisation of plant-based diets both in Ukraine and globally are described. Another line of research is to examine the role of the catering industry in introducing local ingredients and functional dishes to support the population in the context of post-war reconstruction in Ukraine.